Small intestinal bacterial overgrowth syndrome - Bureš, Jan; Cyrany, Jiří; Kohoutová, Darina; Förstl, Miroslav; Rejchrt, Stanislav; Květina, Jaroslav; Vorisek, Viktor; Kopáčová, Marcela (World journal of gastroenterology, 2010)
Human intestinal microbiota create a complex polymicrobial ecology. This is characterised by its high population density, wide diversity and complexity of interaction. Any dysbalance of this complex intestinal microbiome, both qualitative and quantitative, might have serious health consequence for a macro-organism, including small intestinal bacterial overgrowth syndrome (SIBO). SIBO is defined as an increase in the number and/or alteration in the type of bacteria in the upper gastrointestinal tract. There are several endogenous defence mechanisms for preventing bacterial overgrowth: gastric acid secretion, intestinal motility, intact ileo-caecal valve, immunoglobulins within intestinal secretion and bacteriostatic properties of pancreatic and biliary secretion. Aetiology of SIBO is usually complex, associated with disorders of protective antibacterial mechanisms (e.g. achlorhydria, pancreatic exocrine insufficiency, immunodeficiency syndromes), anatomical abnormalities (e.g. small intestinal obstruction, diverticula, fistulae, surgical blind loop, previous ileo-caecal resections) and/or motility disorders (e.g. scleroderma, autonomic neuropathy in diabetes mellitus, post-radiation enteropathy, small intestinal pseudo-obstruction). In some patients more than one factor may be involved. Symptoms related to SIBO are bloating, diarrhoea, malabsorption, weight loss and malnutrition. The gold standard for diagnosing SIBO is still microbial investigation of jejunal aspirates. Non-invasive hydrogen and methane breath tests are most commonly used for the diagnosis of SIBO using glucose or lactulose. Therapy for SIBO must be complex, addressing all causes, symptoms and complications, and fully individualised. It should include treatment of the underlying disease, nutritional support and cyclical gastro-intestinal selective antibiotics. Prognosis is usually serious, determined mostly by the underlying disease that led to SIBO.
Keywords: Blind Loop Syndrome; Diagnosis, Differential; prognóza; Intestine, Small; Prognosis; diferenciální diagnóza; dechové testy; lidé; syndrom slepé kličky; Breath Tests; tenké střevo; Humans